Efecto de tres niveles de agua de mar sobre los parámetros productivos de pollos de engorde línea cobb 500 - Guevara Gutiérrez, Lelis Masuli (2015)
The present investigation was conducted at the La Esperanza, Province of Trujillo, La Libertad district; with the objective of determine the effect of three levels of seawater on growth performance of broiler chickens line Cobb 500. Were used 240 in four treatments, under a completely randomized design. The treatments were: T0: Drinking water without seawater, T1: 150 mL seawater / gal drinking water, T2: 250 mL seawater / gal drinking water and T3: 350 mL of water Sea / gal drinking water. Seawater was subjected to 80 ° C for 3 to 5 minutes before the supply to chickens. The results were statistically evaluated with ANOVA, Duncan test and Chi-Square. Highly significant statistical differences (P<0.01) for final weight and weight gain were calculated, with higher values of T2 (2.64 kg and 2.59 kg); and the lowest values of T0 (2.33 kg and 2.28 kg). For total food consumption, highly significant statistical difference (P<0.01) was determined; being better the T2 (4.45 kg) and worse T0 (4.05 kg). The feed conversion ratio, statistically significant differences (P>0.05) were not calculated but if numeric, being better the value of T2 with 1.72. For the percentage of mortality, T3 won 0% and the other treatments gained 1.67%, without differentiating statistically (P>0.05). The rate of production efficiency for the best value T2 obtained with 359.35 followed by T3, T1 and T0. For the benefit/cost best value is obtained T2 with 1.42 followed by 1.33; 1.37 and 1.38 for T0, T1 and T3 respectively. We conclude that the addition of seawater into drinking water improves growth performance of broilers Cobb 500, still the best treatment T2.